The Relevance of Royce - Bell, Jason; Parker, Kelly A., 1963- (Book collections on Project MUSE., 2014)
'The Relevance of Royce' is a collection of essays from contemporary philosophers engaged in exploring Josiah Royce's work within the light of contemporary philosophical concerns. The collection explores the wide range of Royce studies, treating such familiar themes as the conception of the individual and the community, the nature of religious faith, and his conception of loyalty. Several contributors focus on Royce's ethics as his chief contribution to philosophy.